PEMBELAJARAN AFEKTIF MERUPAKAN SALAH SATU STRATEGI DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK (Sebuah Tinjauan dari Perspektif Psikologi; Social Cognitive Theory) (Jurnal Pelangi : Research of Education and Development, 2014)
According to educational development at this time, education not only transfer of knowledge for student but more than that. Education is to create a generation which have a good abilities, good capabilities and good character, in other word create the cognitive, affective and psychomotor aspect. The phenomena of education at this time, found that proccess of education is still far from build a affective and character of student. Until now a government program of education “education with a character” still not have a product which suitable with the term of program. Also a curriculum of education still focus to create abilities in cognitive student. So the questions is, how to educate the student about affective capabilities? And is this aspect of psychology in education proccess, will build a character of student? The answers of that questions will discribe using perspective of psychology; social cognitive theory.